Academician Ivan Stepanovich Kolesnikov (1901–1985) (on the 120th anniversary of the birth) - I. I. Dzidzava; B. N. Kotiv; A. A. Kurygin; V. I. Iontsev; O. V. Barinov; I. V. Dmitrochenko (Вестник хирургии имени И.И. Грекова)
Received 25.02.2022; accepted 09.03.2022 An outstanding Soviet surgeon, one of the founders of military field surgery – participant in six wars, Hero of Socialist Labor (1976), academician of the USSR Academy of Medical Sciences (1971), Honored Scientist of the RSFSR (1964), laureate of the Lenin Prize (1961) and the USSR State Prize (1985), Major General of the Medical Service (1953), Professor Ivan Stepanovich Kolesnikov was born on December 2 (15), 1901 in the village of Podosinovka, Novokhopersky District, Voronezh Province. In 1931, he graduated from the Military Medical Academy, in 1932 he entered the adjunct course at the Department of Hospital Surgery of the Military Medical Academy headed by Professor S. P. Fedorov, and in 1936, defended his PhD thesis «Transfusion of conserved blood». During the Great Patriotic War, he held the positions of army surgeon and chief surgeon of the Karelian Front. Together with P. A. Kupriyanov, in the period from 1946 to 1955, he published the «Atlas of Gunshot Wounds» in 10 volumes. In 1946, he defended his doctoral dissertation on the topic: «Removal of foreign bodies from the pleural cavity, pleural junctions and indurations, lungs and mediastinum». In 1953, I.S. Kolesnikov was appointed head of the Department and Clinic of Hospital Surgery of the Military Medical Academy, since 1976 – professor-consultant of the Academy. He was the author and co-author of more than 170 scientific papers, including 25 monographs, manuals and textbooks. Under his leadership, 26 doctoral and 43 candidate dissertations were prepared and defended. I.S. Kolesnikov is rightfully recognized as the founder of the national scientific school of thoracic surgery and one of the world luminaries of military field surgery. Academician Ivan Stepanovich Kolesnikov died on May 18, 1985 and was buried at the academic site of the Theological Cemetery in Saint Petersburg.